Geobacillus zalihae sp. nov., a thermophilic lipolytic bacterium isolated from palm oil mill effluent in Malaysia - Raja Noor Zaliha Raja Abd Rahman; Thean Chor Leow; Abu Bakar Salleh; Mahiran Basri (2007)
Thermophilic Bacillus strains of phylogenetic Bacillus rRNA group 5 were described as a new genus Geobacillus. Their geographical distribution included oilfields, hay compost, hydrothermal vent or soils. The members from the genus Geobacillus have a growth temperatures ranging from 35 to 78°C and contained iso-branched saturated fatty acids (iso-15:0, iso-16:0 and iso-17:0) as the major fatty acids. The members of Geobacillus have similarity in their 16S rRNA gene sequences (96.5–99.2%). Thermophiles harboring intrinsically stable enzymes are suitable for industrial applications. The quest for intrinsically thermostable lipases from thermophiles is a prominent task due to the laborious processes via genetic modification. Twenty-nine putative lipase producers were screened and isolated from palm oil mill effluent in Malaysia. Of these, isolate T1T was chosen for further study as relatively higher lipase activity was detected quantitatively. The crude T1 lipase showed high optimum temperature of 70°C and was also stable up to 60°C without significant loss of crude enzyme activity. Strain T1T was a Gram-positive, rod-shaped, endospore forming bacterium. On the basic of 16S rDNA analysis, strain T1T was shown to belong to the Bacillus rRNA group 5 related to Geobacillus thermoleovorans (DSM 5366T) and Geobacillus kaustophilus (DSM 7263T). Chemotaxonomic data of cellular fatty acids supported the affiliation of strain T1T to the genus Geobacillus. The results of physiological and biochemical tests, DNA/DNA hybridization, RiboPrint analysis, the length of lipase gene and protein pattern allowed genotypic and phenotypic differentiation of strain T1T from its validly published closest phylogenetic neighbors. Strain T1T therefore represents a novel species, for which the name Geobacillus zalihae sp. nov. is proposed, with the type strain T1T (=DSM 18318T; NBRC 101842T). Strain T1T was able to secrete extracellular thermostable lipase into culture medium. The strain T1T was identified as Geobacillus zalihae T1T as it differs from its type strains Geobacillus kaustophilus (DSM 7263T) and Geobacillus thermoleovorans (DSM 5366T) on some physiological studies, cellular fatty acids composition, RiboPrint analysis, length of lipase gene and protein profile.